Comparison of the frequency and the occurrence of antimicrobial resistance among C. jejuni and C. coli isolated from human infections, retail poultry meat and poultry in Zenica-Doboj Canton, Bosnia and Herzegovina - Ingrid Berce; Tina Zorman; Selma Uzunović-Kamberović; Lieve Herman; Sonja Smole Možina (Medicinski Glasnik, 2009)
Aim To compare the frequency of isolation and occurrence of antimicrobialresistance among C. jejuni and C. coli isolated in humans,retail poultry meat and poultry.Methods Fifty-three human, 52 retail poultry meat and 15 poultryCampylobacter jejuni/coli isolates were investigated for antibioticsusceptibility to eight antimicrobials by disk-diffusion method.Erythromycin and ciprofloxacin susceptibility were further determinedby E-test, and additionally the MICs of erythromycinand ciprofloxacin were determined using the broth microdilutionmethod.Results Prevalence of C. coli in humans, retail poultry meat andpoultry was 28.3%, 56.9% and 53.3%, respectively. No significantdifferences were found in the overall resistance rates between C.jejuni and C. coli isolated from all three sources (p>0.05). Erythromycinand ciprofloxacin resistance was high and similar in humans,retail poultry meat and poultry (26.4%, 35.3%, 26.7%, and32.1%, 23.5%, 26.7%, respectively) (p>0.05). C. jejuni displayedhigher prevalence of resistance to erythromycin than C. coli inall investigated sources (p>0.05). All ciprofloxacin and 94.4% oferythromycin positive isolates were highly resistant (≥ 32 μg/mLand ≥128 μg/mL, respectively).Conclusion The high prevalence of C. coli isolates from humans,poultry meat and poultry and higher both overall and erythromycin-resistance in C. jejuni than in C. coli isolates suggests that theremay be a common source in the environment, which might be absentin other geographical regions. Further studies are requiredto determine the role of efflux mechanism in erythromycin- andciprofloxacin-resistance related to the level of resistance.